Challenges and opportunities of disaster education program among UUM student - Chong, Khai Lin; Abdul Nifa, Faizatul Akmar; Musa, Suria; Shahron, Syairah Aimi; Anuar, Nur Anisah (IP Publishing LLC, 2018)
“Disaster education” is a new area and concepts in the field of education in Malaysia. UUM students are less exposed to Disaster education compared with students in the other country. Nowadays, there have been significant increases in the frequency of the disasters. The goals of this research are given knowledge for UUM student to prevent, prepared and more aware of the future disaster. Providing UUM students with disaster education is one of the steps towards the creating of the culture of prevention and preparedness within each other. The aimed of this study on “Disaster Education” is for reducing vulnerabilities to natural hazards and makes people more aware of the natural disaster. The importance of disaster education is for reducing disaster and achieves safety of human for sustainable development among university students. Based on these literature findings, the questionnaires were conducted among UUM students to explore the challenges and opportunity of Disaster Education Program among UUM students. The objective of this research is to present the questionnaire findings on challenges and opportunities of disaster education among UUM students is related to the disaster knowledge factors. A comprehensive list of challenges and opportunities for disaster education program among UUM students is identified from this research.